A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980 - Li, Weihai; Liu, Ruijun (Zootaxa, 2019)
A new species of the perlid genus Neoperla from Tibet of China is described, N. tibetensis sp. nov. The new species is compared with related taxa. The fully everted aedeagal sac of N. perspicillata Zwick, 1980 is illustrated from a male from Nepal.